Pengaruh Kualitas Produk, Ekuitas Merek dan Celebrity Endorser Terhadap Keputusan Pembelian Produk Kosmetik Maybelline: Studi pada Konsumen Produk Kosmetik Maybelline di Kota Kendal - Laili Setianita Rizki; Euis Soliha (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to determine the influence of quality, equity and celebrity endorsers on purchasing decisions for Maybelline cosmetic products . The method used in this research is to use a quantitative method, which means a form of data in the form of numbers. The results state that product quality has a positive and significant effect on purchasing decisions. It can be interpreted that the better and better the quality of a product, the more interested consumers will be in deciding to buy Maybelline cosmetic products. Brand equity has a positive and significant effect on purchasing decisions. It can be interpreted that the better the level of equity of a product, the more interested consumers will be in deciding to buy Maybelline cosmetic products. Celebrity endorsers have a positive and significant influence on purchasing decisions. It can be interpreted that the better and more attractive the advertisement being promoted, the more interested consumers will be in deciding to buy Maybelline cosmetic products.